"Knuckle-Dragging Thugs": civilizing processes and the biosocial revolution in the National Hockey League - Kennedy, Liam (Crime, media, culture, 2021)
In this article, we advocate for the development of a critical criminology of sport. To this end, we analyze news media coverage of a sample of National Hockey League suspensions to explore how the sporting world disseminates cultural messages about crime and punishment. Our analysis reveals that athlete "offenders" are likened to Lombrosian evolutionary throwbacks whose brutal on-ice violence recalls a less civilized past. Images of blood spilled on the ice and bodies carried away on stretchers shock our sensibilities. We argue that, as the arbiter of supplemental discipline, the National Hockey League regulates the bodies under its control and aims to signify that hockey and its fans are encapsulated in what Elias famously calls civilizing processes rather than mere barbaric sporting games. We situate these findings in the reemergence of a bio(social) criminology and express concerns regarding the spread of this rhetoric.